Edukasi Siswa SMA Negeri 2 Mojokerto Kelola Keuangan Pribadi Berbasis Akuntansi - Risa Watti; Djojo Dihardjo; Nurul Azizah (Lembaga Pengembangan Kinerja Dosen, 2025)
Personal financial management is an essential skill that needs to be instilled from adolescence to foster healthy and responsible financial behavior. Teenagers are often faced with situations where they must make decisions regarding money, but a lack of understanding and education about finances often leads to consumptive behavior, wastefulness, and a lack of ability to save. However, poor financial habits developed early on can carry over into adulthood and impact a person's future financial situation. Through a Community Service activity conducted by lecturers from the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya (FEB UWKS) at SMA Negeri 2 Mojokerto, students were provided with education on accounting-based personal financial management. The material presented covered basic accounting principles, the importance of recording income and expenses, and how to prepare a personal financial budget. The activity methods included counseling, financial recording simulations, budget preparation, and interactive discussions, designed to encourage active participation and practical understanding. The results of the activity showed that students experienced a significant increase in understanding of the importance of financial literacy. They were also able to prepare a simple budget based on needs and priorities using a basic accounting approach. Thus, this activity is expected to make a real contribution to shaping the character, responsibility, and financial independence of the younger generation. Furthermore, similar activities can be extended to other schools to raise financial literacy awareness among students more broadly and sustainably. Furthermore, the involvement of teachers and school administrators in supporting this financial literacy program is also a crucial factor in maintaining students' desire to understand. With synergy between academics, schools, and students, financial education can become an integral part of the learning process, focusing not only on theory but also on practical application in everyday life.